Hyperactive Behavior and Altered Brain Morphology in Adult Complement C3a Receptor Deficient Mice - Pozo-Rodrigálvarez, Andrea; Ollaranta, Roosa; Skoog, Jenny; Pekny, Milos; Pekna, Marcela (Frontiers in Immunology, 2021)
The C3a receptor (C3aR) is a seven trans-membrane domain G-protein coupled receptor with a range of immune modulatory functions. C3aR is activated by the third complement component (C3) activation derived peptide C3a and a neuropeptide TLQP-21. In the central nervous system (CNS), C3aR is expressed by neural progenitors, neurons as well as glial cells. The non-immune functions of C3aR in the adult CNS include regulation of basal neurogenesis, injury-induced neural plasticity, and modulation of glial cell activation. In the developing brain, C3aR and C3 have been shown to play a role in neural progenitor cell proliferation and neuronal migration with potential implications for autism spectrum disorder, and adult C3aR deficient (C3aR-/-) mice were reported to exhibit subtle deficit in recall memory. Here, we subjected 3 months old male C3aR-/- mice to a battery of behavioral tests and examined their brain morphology. We found that the C3aR-/- mice exhibit increased locomotor activity in the open field and object recognition test, but do not show any signs of autistic behavior as assessed by self-grooming behavior. The C3aR-/- mice have a short-term memory deficit and faster memory extinction. We also found regional differences between the C3aR-/- and wild-type (WT) mice in the morphology of motor and somatosensory cortex, as well as amygdala and hippocampus. In summary, constitutive absence of C3aR signaling in mice leads to neurodevelopmental abnormalities that persist into adulthood and are associated with locomotive hyperactivity and altered cognitive functions.